Water, Sediment and Macrophyte Quality of Some Shrimp Culture Ponds and Freshwater Ecosystems of Koyra - Chowdhury, Abdullah Harun; Ahmed, Roxana (Bangladesh Journal of Botany, 2012)
A total of 29 genera belonging to 24 families of aquatic macrophytes were recorded. Among these, 25 species were recorded from the freshwater aquatic ecosystems, 4 species from both the shrimp culture ponds and freshwater aquatic ecosystems and only one from the shrimp culture ponds. The physicochemical conditions of both the habitats indicate that very poor number of macrophytes can grow in the shrimp culture ponds due to high salinity of water and soil. Low population and abundance indicate that the macrophytes are in alarming condition in Koyra due to increasing salinity. DOI: http://dx.doi.org/10.3329/bjb.v41i1.11080 Bangladesh J. Bot. 41(1): 35-41, 2012 (June)